Tingkat kesesuaian self-reported bruxism sebelum dan sesudah observasi mandiri (Laporan Penelitian) - Michelle Sanita; Siti Chandra Dwidjayanti; Carolina Damayanti Marpaung (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Bruxism is considered to be a common condition among the adult population, although data on bruxism are still rare. Bruxism is repetitive jaw activity during sleep (sleep bruxism) and awake (awake bruxism). In healthy individuals, bruxism should not be regarded as a disorder, but as a behavior that can be a risk factor for certain clinical conditions. Several studies have stated that the accuracy of self-reported bruxism is low because the individual is less aware of the behavior. Aim: To find out the concordance of the results of self-reported bruxism before and after self-observation. Methods: The type of research used in this research is analytic observational using a cross-sectional research design. The data was obtained by distributing questionnaires via a google form link to 142 FKG Usakti students class 2020. Inter Class Correlation (ICC) was calculated to assess the concordance between the two assessments using five items of Oral Behavior Checklist questionnaire (OBCL). Results: High concordance was shown between assessment prior and after self observation. The ICC results range from 0.636 to 0.838 for five items of OBCL Conclusion: There is a high concordance between the results of self-reported bruxism before and after self-observation.